Neglected cervical spondyloptosis of the 5TH – 6TH cervical spine following cervical manipulation: A case report - Sakti, Yudha Mathan; Anzhari, Sharfan; Kartika, Andrea; Irfantian, Ardicho; Ahmad, Husein; Sakadewa, Galih Prasetya; Alhaq, Zaky Asad; Resubun, Alan Philips Kustianto Putra; Tarsan, Karsapin (Elsevier Ltd, 2022)
A 16-year-old boy was diagnosed with spondyloptosis of the cervical spine at the C5–6 level with a neurologic deficit following cervical manipulation. He could not move his upper and lower extremities, but the sensory and autonomic function was spared. The pre-operative American Spinal Cord Injury Association (ASIA) Score was B with SF-36 being 25%, and Karnofsky's score was 40%. The patient was disabled and required special care and assistance. We performed anterior decompression, cervical corpectomy at the level of C6 and lower part of C5, deformity correction, cage insertion, bone grafting, and stabilization with an anterior cervical plate. The patient's objective functional score had increased after six months follow up and assessed objectively with the ASIA Impairment Scale (AIS) E or Excellent, SF-36 score 94%, and Karnofsky score was 90%. The patient could carry on regular activity with minor signs or symptoms of the disease. This case report highlights severe complications following cervical manipulation, a summary of the clinical presentation, surgical treatment choices, and a review of the relevant literature. In addition, the sequential improvement of the patient's functional outcome after surgical correction will be discussed. © 2022 The Authors